Implications of Corona Virus Disease-19 pandemic on cytopathology laboratory—Challenges and solutions in resource-limited settings - Smita Chandra; Anuradha Kusum; Dushyant Singh Gaur (Indian Journal of Pathology and Microbiology, 2023)
Background: Corona Virus Disease-19 (COVID-19) disease which is still showing peaks and plateau with emerging new mutational viral variants has led to the modification of working of hospitals and medical institutes. Cytopathology laboratories geared up with the changing situation to cope up with not only the COVID-19 patients but also patients of other diseases, particularly oncology patients. It was also important to adopt changes in the cytopathology residency program so as to cope up with the changing scenario. Aim: The present study was conducted to study the various measures adopted and the changes made in the cytopathology laboratory during COVID-19 infection in a resource-limited setting while catering to a large population of COVID-19-positive patients in the north Himalayan region of India. It was also intended to study the methods adopted for effective cytopathology residency training during corona times. Setting and Design: The study was conducted from March 2020 to December 2021 in the cytopathology lab, and all the samples were analyzed and compared with the samples received in pre-corona times from March 2018 to December 2019. The different methods adopted during corona times for effective cytopathology residency training were also analyzed. Results: The total number of samples received in the cytopathology laboratory in pre-corona times from March 2018 to December 2019 were 6822, and samples received from March 2020 to December 2021 were 6567 with decrease of 1.9% of cases. There was increase in 17.4% for the samples of the respiratory tract received in the lab with an increase in cases of infections including aspergillosis, mucormycosis, and tuberculosis. There was 10.3% increase in cytological diagnosis of malignant cases during corona times. Use of 90% alcohol for fixation rather than air drying of smears, avoiding of pneumatic tubes, judicious use of personal protective equipment (PPE) kits along with access to the digital cytology slide database were included in the changes made in the lab. Conclusions: There was a marginal decrease in cytopathological diagnosis during COVID-19 with substantial increase in the malignancy rate of 10.3% in cytological diagnosis of different organs. Diagnosis of mucormycosis, aspergillosis, and tuberculosis infections of respiratory tract cytology increased during this period. Judicious use of limited available resources led not only to smooth functioning of the cytopathology lab but also prevented any infection in the working health personals. Newer online resources were explored and modified for continuous training of the cytopathology residents. Emotional support with effective communication was the key to alleviate any psychological stress among all health professionals in the cytopathology laboratory.